DFT study on some polythiophenes containing benzo[d]thiazole and benzo[d]oxazole: structure and band gap - Trung Vu Quoc (Designed Monomers and Polymers, 2021)
The content of this paper focuses/shed light on the effects of X (X = S in P1 and X = O in P2) in C11H7NSX and R (R = H in P3, R = OCH3 in P4, and R = Cl in P5) in C18H9ON2S2-R on structural features and band gaps of the polythiophenes containing benzo[d]thiazole and benzo[d]oxazole by the Density Function Theory (DFT) method/calculation. The structural features including the electronic structure lattice constant (a), shape, total energy (Etot) per cell, and link length (r), are measured via band gap (Eg) prediction with the package of country density (PDOS) and total country density (DOS) of material studio software. The results obtained showed that the link angle and the link length between atoms were not changed significantly while the Etot was decreased from Etot = – 1904 eV (in P1) to Etot = – 2548 eV (in P2) when replacing O with S; and the Etot of P3 was decreased from Etot = – 3348 eV (in P3) when replacing OCH3, Cl on H of P3 corresponding to Etot = – 3575 eV (P4), – 4264 eV (P5). Similarly, when replacing O in P1 with – S to form P2, the Eg of P1 was dropped from Eg = 0.621 eV to Eg = 0.239 eV for P2. The Eg of P3, P4, and P5 is Eg = 0.006 eV, 0.064 eV, and 0.0645 eV, respectively. When a benzo[d]thiazole was added in P1 (changing into P3), the Eg was extremely strongly decreased, nearly 100 times (from Eg = 0.621 eV to Eg = 0.006 eV). The obtained results serve as a basis for future experimental work and used to fabricate smart electronic device.